KAJIAN FENOMENOLOGI TERHADAP PAK ONLINE BAGI KAUM LANSIA DI GSRI JAKARTA DALAM MASA PANDEMI COVID-19 - Tahapan Deddy Zulfian Sinaga (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2021)
This study examines the perceptions and experiences of the elderly in providing online Christian religious education in churches as a result of social restrictions during the COVID-19 pandemic. The research subjects were the elderly at the Santapan Rohani Indonesia Church (GSRI) Jakarta. The method used is qualitative with a phenomenological approach. Data analysis used the technique proposed by Clark Moustakas, namely the synthesis and essence of meaning. The study results show that the elderly can enjoy online Christian religious education programs at the church even though they experience several challenges and limitations. Christian religious education activities online at the church can also meet the spiritual needs of the elderly. But to take part in such online activities requires extraordinary focus and sincerity. The online activities also cannot provide elements of face-to-face activities that they yearn for, so the elderly hope that the situation will improve soon and quickly return to face-to-face church activities.